A Rare Case of Atrophic Dermatofibroma Featuring Linear Skin Dimple - Madoka Takafuji; Atsushi Tanemura; Yuma Hanaoka; Katsuto Tamai; Manabu Fujimoto (Karger Publishers, 2019)
Dermatofibroma (DF) is a benign skin tumor that is well-known among dermatologists. We herein present a rare case of atrophic dermatofibroma presenting linear skin dimpling. The patient was a 25-year-old woman with a history of wild-type recessive dystrophic epidermolysis bullosa who had noticed linear concavity on her right lateral back 1 year before her initial presentation. Anetoderma, atrophic scar, localized morphea, or lupus erythematosus profundus were clinically suspected; however, a biopsy specimen from the dimpling lesion showed the fibrous and histiocytic tumor in the deep dermis. The spindle-to-rhomboid-shaped tumor cells were arranged with irregularly storiform pattern, and immunohistochemistry showed that the tumor cells were positive for factor XIIIa, and negative for CD34 and CD68. Elastica van Gieson staining showed an almost complete loss of elastic fibers, especially at the center of the lesion. The reduction of elastic fibers might have influenced the skin depression in this case. This rare case suggests the need to consider a subtype of DF in the differential diagnosis of dimpling skin lesions.